Initial experience of a novel surgical assist robot “Saroa” featuring tactile feedback and a roll-clutch system in radical prostatectomy - Kosuke Iwatani; Fumihiko Urabe; Shun Saito; Shota Kawano; Tomoya Yamasaki; Shoji Kimura; Hideo Otsuki; Kei Fujio; Takahiro Kimura; Jun Miki (Scientific Reports)
Abstract To evaluate the safety and efficacy of the Saroa Surgical Robot System in robot-assisted laparoscopic radical prostatectomy (RARP). We enrolled 60 patients who underwent RARP using either the Saroa (n = 9) or da Vinci Xi (n = 51) systems at Jikei University Kashiwa Hospital from January 2022 to March 2024. We compared preoperative characteristics, perioperative outcomes, complications, and postoperative urinary continence at three months between the two groups. No significant differences were found in preoperative characteristics. The Saroa group had a longer median operative time compared to the da Vinci group. Postoperative urinary continence rates were slightly lower in the Saroa group (77.8 % vs. 84.6%), though not statistically significant. When the tactile feedback function was activated, the organs were grasped with less force compared to when it was off. This study is the first to assess the Saroa system’s effectiveness and safety in RARP. While the system shows promise, especially with tactile feedback that aids in delicate tissue handling, further investigation is needed to evaluate long-term oncological and functional outcomes.